Radiologic Sciences Student Perceptions of Advisement. - Street Beam, Asher; Brown, Lee; Ketchum, James M.; Edgerton, Shazowee; Palmer Stephens, Chelsea; Gray, Zack; Ratcliff, Molly; Moore, Kristi (Radiologic Technology)
Purpose To investigate student perceptions of a structured advisement program. Methods Using a mixed-methods approach, 24 radiologic sciences students were surveyed in the initial and final semesters of the program to capture their perceptions of advisement practices. Quantitative data were analyzed for percentages and descriptive statistics, and qualitative responses were analyzed for emergent themes. Results Qualitative data analyses identified 3 themes: building relationships, strengthening student performance, and determining best practices for advisement. Quantitative data demonstrated that students appreciated the advisement process and acknowledged improvements in communication skills and the feedback loop. Discussion Advisement sessions can serve an important role in identifying areas where students can improve their performance. To grow and develop, students must understand their own strengths and weaknesses. Structured forms of advisement can serve as important tools to guide advisement conversations toward specific topics. Conclusion The results of this study indicate that student advising is a vital component of radiologic sciences programs. Participants indicated that the advisement process helped them build relationships with faculty members and improved their overall performance.